Efficient Solution of Point-Line Absolute Pose - Hruby, Petr; Duff, Timothy; Pollefeys, Marc (CVPR 2024, 2024)
We revisit certain problems of pose estimation based on 3D–2D correspondences between features which may be points or lines. Specifically, we address the two previously-studied minimal problems of estimating camera extrinsics from p \[ 1, 2 \] point–point correspondences and l=3-p line–line correspondences. To the best of our knowledge, all of the previously-known practical solutions to these problems required computing the roots of degree 4 (univariate) polynomials when p=2, or degree 8 polynomials when p=1. We describe and implement two elementary solutions which reduce the degrees of the needed polynomials from 4 to 2 and from 8 to 4, respectively. We show experimentally that the resulting solvers are numerically stable and fast: when compared to the previous state-of-the art, we may obtain nearly an order of magnitude speedup. The code is available at [https://github.com/petrhruby97/efficient_absolute]